1990
DOI: 10.1111/j.2042-7158.1990.tb05369.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of catecholamines on cholinergically and non-cholinergically mediated contractions of guinea-pig isolated bronchial muscle

Abstract: The actions of catecholamines on the responses evoked by electrical field stimulation or by acetylcholine and substance P in guinea-pig bronchial strip chain have been examined. Electrical field stimulation evoked a biphasic contraction, consisting of a cholinergically-mediated fast contraction followed by a non-cholinergically-mediated slow contraction. All catecholamines tested caused a concentration-dependent reduction in the height of the biphasic contraction, where non-cholinergic contractions were more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…Moreover, these agonists were more effective than BRL 38227 at producing relaxation of ACh-induced spasm of the bronchial smooth muscle (Figure 4). These findings show good agreement with previous work using ketotifen and isoprenaline (Kamikawa, 1989;Kamikawa & Shimo, 1990) (Mondot et al, 1990), are each thought to cause smooth muscle relaxation by opening K+-channels in the plasmalemma of smooth muscle cells (Bray et al, 1987;Arch et al, 1988;Mondot et al, 1988 (Ashcroft, 1988). At higher concentrations, it has been shown to block an ATP-dependent K+-channel opened by cromakalim in rabbit mesenteric arterial smooth muscle cells (Standen et al, 1989).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, these agonists were more effective than BRL 38227 at producing relaxation of ACh-induced spasm of the bronchial smooth muscle (Figure 4). These findings show good agreement with previous work using ketotifen and isoprenaline (Kamikawa, 1989;Kamikawa & Shimo, 1990) (Mondot et al, 1990), are each thought to cause smooth muscle relaxation by opening K+-channels in the plasmalemma of smooth muscle cells (Bray et al, 1987;Arch et al, 1988;Mondot et al, 1988 (Ashcroft, 1988). At higher concentrations, it has been shown to block an ATP-dependent K+-channel opened by cromakalim in rabbit mesenteric arterial smooth muscle cells (Standen et al, 1989).…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, Martin & Collier (1986) could not demonstrate that the P-adrenoceptor agonist, noradrenaline, inhibited the release of acetylcholine from cholinergic nerves in canine airways. Other studies (Kamikawa & Shimo, 1990;Verleden et al, 1991) have also previously demonstrated the inhibitory effects of noradrenaline and P2-adrenoceptor agonists (formoterol, salbutamol) on the EFS-induced NANC contraction in guinea-pig bronchi. Our present study is consistent with a postjunctional mechanism of salbutamol since we observed an inhibitory effect of this compound on cumulative concentration-response curves to acetylcholine, substance P and , the latter compound being a selective agonist of NK2-receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of salbutamol were abolished or inhibited by both the nonselective P-adrenoceptor antagonist, propranolol, and by the selective ICI 118,551, showing that the effects of salbutamol are due to stimulation of P2-adrenoceptors. The inhibitory effects of P-adrenoceptor agonists on the cholinergic response induced by EFS or vagal stimulation have previously been described for the guinea-pig isolated bronchus (Kamikawa & Shimo, 1990), the canine isolated bronchus (Cabezas et al, 1971;Vermeire & Vanhoutte, 1979;Martin & Collier, 1986;Danser et al, 1987;Ito, 1988) and for human bronchi (Rhoden et al, 1988;Aizawa et al, 1991) and they have been attributed to prejunctional inhibition because P-adrenoceptor agonists were more effective in inhibiting this response than similar contractile responses induced by exogenous acetylcholine (Vermeire & Vanhoutte, 1979;Ito, 1988;Aizawa et al, 1991). Nevertheless, Martin & Collier (1986) could not demonstrate that the P-adrenoceptor agonist, noradrenaline, inhibited the release of acetylcholine from cholinergic nerves in canine airways.…”
Section: Discussionmentioning
confidence: 99%
“…Their relatively greater thickness, however, favours a contribution by preganglionic and sensory axons. Sensory axons are especially likely candidates, since [32-adrenoreceptor protein and mRNA have been identified by immunohistochemistry and in situ hybridization in dorsal root ganglion neurons (Kloock & Kummer, 1994;Kummer et aI., 1994), and [32-agonists inhibit neuropeptide release from peripheral sensory nerve endings (Kamikawa & Shimo, 1990;Barnes, 1992).…”
Section: Discussionmentioning
confidence: 98%